2015
DOI: 10.1002/kin.20922
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Lab Prepared Manganese Oxide Catalyzed Oxidation of Benzyl Alcohol in the Liquid Phase

Abstract: The oxidation of benzyl alcohol in the liquid phase was studied over manganese oxide catalyst using molecular oxygen as an oxidant. Manganese oxide was prepared by a mechanochemical process in solid state and was characterized by chemical and physical techniques. The catalytic performance of manganese oxide was explored by carrying out the oxidation of benzyl alcohol at 323–373 K temperature and 34–101 kPa partial pressure of oxygen. Benzaldehyde and benzoic acid were identified as the reaction products. Typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The adsorption constant is a function of temperature, the enthalpy and entropy of adsorption, furthermore, the dependence that K ad has on temperature can be determined if the enthalpy of adsorption is known. The determination of the enthalpy or heats of adsorption from the liquid phase has been acknowledged to be more challenging than for adsorption from the gaseous phase In the literature, the studies of isosteric heats of adsorption in the liquid phase have often reported low values . Hence, in the present work it is assumed that the heat of adsorption is relatively low, implying that for the studied temperature range the effect that temperature has on the K ad value is low enough such that it can be considered negligible.…”
Section: Resultsmentioning
confidence: 95%
“…The adsorption constant is a function of temperature, the enthalpy and entropy of adsorption, furthermore, the dependence that K ad has on temperature can be determined if the enthalpy of adsorption is known. The determination of the enthalpy or heats of adsorption from the liquid phase has been acknowledged to be more challenging than for adsorption from the gaseous phase In the literature, the studies of isosteric heats of adsorption in the liquid phase have often reported low values . Hence, in the present work it is assumed that the heat of adsorption is relatively low, implying that for the studied temperature range the effect that temperature has on the K ad value is low enough such that it can be considered negligible.…”
Section: Resultsmentioning
confidence: 95%
“…The kinetics of heterogeneous catalytic reactions can be described in terms of two commonly used mechanisms. [28][29][30][31] 1. The Langmuir-Hinshelwood mechanism 2.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…where [MB] 0 = initial concentration; [MB] t = concentration of MB at time t; k 1 = first-order rate constant; k 2 = second-order rate constant. The degradation data given in Figure 2 were analyzed according to Equations (28) and (29) as given in Figure 7. Table 3 lists the rate constants determined from Figure 7.…”
Section: Catalystmentioning
confidence: 99%
“…As stated earlier, degradation of dyes takes place at the surface of catalyst. The kinetics of surface-catalyzed reaction can be described by one of the three possible mechanisms of heterogenous catalysis [37]:…”
Section: Kinetics Of Wet Catalytic Oxidation/degradationmentioning
confidence: 99%